Peran Mahasiswa KKN dalam Meningkatkan Minat Belajar Pendidikan Agama Islam di MDTA Yayasan Al-Muttaqin - Bintang Ariga (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study aims to determine the role of Community Service Program (KKN) students in increasing interest in learning Islamic Religious Education (PAI) at the Al-Muttaqin Foundation MDTA. The background of this study stems from the low enthusiasm and motivation of students in participating in religious lessons, so that learning innovations are needed that can rekindle their enthusiasm for religious values. KKN students, as part of the implementation of the Tri Dharma of Higher Education, have a social responsibility to contribute directly to society, one of which is through educational activities. In its implementation, students apply various creative, interactive, and fun learning methods, such as educational games, group discussions, and role-model-based approaches that make students more active and motivated. This study uses a descriptive qualitative method with observation, interview, and documentation techniques during the two-month activity. The results show that the presence of KKN students has a positive influence on increasing student interest in learning, seen from increased discipline, active participation, and curiosity about PAI materials. In addition to being teachers, students also play a role as moral guides who instill religious values ​​through positive behavior and habits.